Kesatuan Transenden di Tengah Pluralisme Agama: Sebuah Interpretasi Pemikiran Frithjof Schuon - Theguh Saumantri (UIN Siber Syekh Nurjati Cirebon, 2023)
Indonesia, as a country with a high religious diversity, needs a framework of thought that can accommodate this diversity. The purpose of this study is to discuss Frithjof Schuon's thought on transcendental unity and its relevance to the context of religious life in pluralistic Indonesia. In the context of religious pluralism in Indonesia, Schuon argues that all religions and beliefs have the same roots in transcendental unity that transcend doctrinal or dogmatic differences. This concept has important implications for strengthening unity in diversity in Indonesia, but also poses challenges and criticism. This research is a literature review using a philosophical approach that aims to analyze the ideas of the figure. The results show that Schuon's ideas can provide a relevant framework for addressing the challenges of religious pluralism in Indonesia by teaching tolerance, respect for differences, and a deeper understanding of transcendental reality. The application of Schuon's concept of pluralistic reasoning and transcendental unity can be a basis for building a more harmonious and peaceful society in Indonesia.